The effects of smoking on levels of endothelial progenitor cells and microparticles in the blood of healthy volunteers. - Fariborz Mobarrez; Lukasz Antoniewicz; Jenny A Bosson; Jeanette Kuhl; David S Pisetsky; Magnus Lundbäck (PLoS ONE)
Background Cigarette smoking, both active and passive, is one of the leading causes of morbidity and mortality in cardiovascular disease. To assess the impact of brief smoking on the vasculature, we determined levels of circulating endothelial progenitor cells (EPCs) and circulating microparticles (MPs) following the smoking of one cigarette by young, healthy intermittent smokers. Materials and methods 12 healthy volunteers were randomized to either smoking or not smoking in a crossover fashion. Blood sampling was performed at baseline, 1, 4 and 24 hours following smoking/not smoking. The numbers of EPCs and MPs were determined by flow cytometry. MPs were measured from platelets, leukocytes and endothelial cells. Moreover, MPs were also labelled with anti-HMGB1 and SYTO 13 to assess the content of nuclear molecules. Results Active smoking of one cigarette caused an immediate and significant increase in the numbers of circulating EPCs and MPs of platelet-, endothelial- and leukocyte origin. Levels of MPs containing nuclear molecules were increased, of which the majority were positive for CD41 and CD45 (platelet- and leukocyte origin). CD144 (VE-cadherin) or HMGB1 release did not significantly change during active smoking. Conclusion Brief active smoking of one cigarette generated an acute release of EPC and MPs, of which the latter contained nuclear matter. Together, these results demonstrate acute effects of cigarette smoke on endothelial, platelet and leukocyte function as well as injury to the vascular wall.